Alvin Toffler: knowledge, technology and change in future society - Wan Fariza Alyati Wan Zakaria (Universiti Kebangsaan Malaysia, 2012)
In this article, we attempt at analysing the thoughts of Alvin Toffler. Toffler is a prominent futurist and the proponent of the theory of ‘The Third Wave society’. In his theory, Toffler has explicitly discussed the role of knowledge and technology in effecting changes and thus shaping the coming of the new type of society in the future.